2021
DOI: 10.3389/fonc.2021.646135
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lymphadenectomy During Interval Debulking Surgery Performed After Neoadjuvant Chemotherapy in Patients With Advanced Ovarian Cancer

Abstract: ObjectiveThe role of lymphadenectomy in interval debulking surgery (IDS) performed after neoadjuvant chemotherapy (NACT) in advanced ovarian cancer remains unclear. We aimed to investigate the clinical significance of lymphadenectomy in IDS.MethodsWe retrospectively reviewed and analyzed the data of patients with advanced ovarian cancer who underwent NACT followed by IDS.ResultsIn 303 patients receiving NACT-IDS, lymphadenectomy was performed in 127 (41.9%) patients. One hundred and sixty-three (53.8%) patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 22 publications
(55 reference statements)
3
15
1
Order By: Relevance
“…Of the 303 patients included in the study, 163 (53.8%) patients achieved NGR, and 127 (41.9%) patients underwent lymphadenectomy. The results suggested no therapeutic value of lymphadenectomy, with both PFS and OS showing no statistical difference between the lymphadenectomy group and no lymphadenectomy group ( 16 ). In our study, we did not include patients received neoadjuvant chemotherapy for analysis to avoid bias.…”
Section: Discussionmentioning
confidence: 95%
“…Of the 303 patients included in the study, 163 (53.8%) patients achieved NGR, and 127 (41.9%) patients underwent lymphadenectomy. The results suggested no therapeutic value of lymphadenectomy, with both PFS and OS showing no statistical difference between the lymphadenectomy group and no lymphadenectomy group ( 16 ). In our study, we did not include patients received neoadjuvant chemotherapy for analysis to avoid bias.…”
Section: Discussionmentioning
confidence: 95%
“…No additional eligible studies were retrieved by hand-searching bibliographies. Nine fulfilled the inclusion criteria for this systematic review, involving a total of 1,660 patients [ 32 33 34 35 36 37 38 39 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of included studies are detailed in Table 1 . All nine studies were retrospective [ 32 33 34 35 36 37 38 39 40 ]. No randomized controlled trials were found.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations